(untitled) (Global Journal of Medical Research, 2022)
Ringworm is zoonotic skin disease and one of the most frequently occurring in human and domesticated animals. It is estimated that 20% of the world population is affected by Ringworm. Camel Dermatophytosis has great public health and economic impact that leads to low milk yield, meat production and poor hide quality. A cross-sectional study was carried out to determine the prevalence and risk factors associated with Ringworm infection among One- humped camel (Camelus dromedarius) in Camel farms of Benadir Region, Somalia. 384 camels surveyed from camel farms randomly were screened in Ringworm infection. 54 camels (14%) were clinically suspected by examining skin scrapings in 20% KOH for detection of Ringworm under the microscope. Among this 29 camels (7.5%) were infected with Ringworm. According to the age group the highest prevalence was recorded camels younger than 3 years.